2010
DOI: 10.1111/j.1439-0507.2009.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitroactivity of voriconazole against Mexican oral yeast isolates

Abstract: Oral candidiasis is the most prevalent complication in HIV-infected and AIDS patients. Topical antifungal treatment is useful for the initial episodes of oral candidiasis, but most patients suffer more than one episode and fluconazole or itraconazole can help in the management, and voriconazole may represent a useful alternative agent for the treatment of recalcitrant oral and oesophageal candidiasis. The aim of this research was to study the in vitro activity of voriconazole and fluconazole against Mexican or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
2
Order By: Relevance
“…As shown in Table4, Voriconazole (VCZ) was the most effective drug in vitro with GMMICs of 0.957 𝜇g/ml, for C. albicans,Omran et al (2018) in Iran previously showed that the GM-MIC90 for Voriconazole (VCZ ) were 0.25 𝜇g/ml for C. albicans less than our findings[36]. Several other studies also demonstrated that Voriconazole (VCZ) was strong antifungal agents against Candida spp [36,[54][55][56][57]…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…As shown in Table4, Voriconazole (VCZ) was the most effective drug in vitro with GMMICs of 0.957 𝜇g/ml, for C. albicans,Omran et al (2018) in Iran previously showed that the GM-MIC90 for Voriconazole (VCZ ) were 0.25 𝜇g/ml for C. albicans less than our findings[36]. Several other studies also demonstrated that Voriconazole (VCZ) was strong antifungal agents against Candida spp [36,[54][55][56][57]…”
contrasting
confidence: 58%
“…In the current study, 5% of However, the geometric MIC90 was 0.957 𝜇g/mL which is the lowest MIC90 for all tested drugs; the good in vitro activities of Voriconazole (VCZ) in the current study have been previously reported against Candida spp. obtained from oral candidacies patients[54][55][56]. As shown in Table4, Voriconazole (VCZ) was the most effective drug in vitro with GMMICs of 0.957 𝜇g/ml, for C. albicans,Omran et al (2018) in Iran previously showed that the GM-MIC90 for Voriconazole (VCZ ) were 0.25 𝜇g/ml for C. albicans less than our findings[36].…”
contrasting
confidence: 53%
“…Antifungal testing of oral yeast isolates are crucial for the selection of antifungal agents and the prediction of clinical response in patients with HIV/AIDS [20,26]. In this study, we tested the antifungal activities of four widely used drugs in Kunming on yeast isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study have shown that HAART decreased the incidence of all HIV-related opportunistic infections including fungal infection [16], but there are conflicting reports regarding the association between oral yeast colonization and HAART [6,7,17-19]. Monitoring the antifungal susceptibility of clinical isolates from patients with HIV/AIDS has crucial importance for better treatment of these patients [20]. …”
Section: Introductionmentioning
confidence: 99%